VD_FINDINFO HC / 2012 / 274 vom 27. Februar 2012 - VD Tribunal cantonal (2012)
SOCIÉTÉ COOPÉRATIVE, STATUTS, INDEMNITÉ ÉQUITABLE, SORTIE, ABUS DE DROIT | 2 al. 2 CC, 8 CC, 842 al. 2 CO, 842 al. 3 CO, 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)